2023
DOI: 10.1108/joepp-08-2022-0237
|View full text |Cite
|
Sign up to set email alerts
|

Electronic human resource management (e-HRM) configuration for organizational success: inclusion of employee outcomes as contextual variables

Abstract: PurposeThe purpose of this paper is to examine whether employee outcomes of employee performance and job satisfaction mediate and enhance the effect of e-HRM usage on organizational performance.Design/methodology/approachData were collected through a survey involving 35 organizations using e-HRM systems. A partially mixed sequential dominant status explanatory design was used for the study. A stratified convenience sampling technique was used for the quantitative phase of the study. A purposive sampling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Nyathi et al [40] Divide the HRM system into three categories: philosophy, practices, and policy. "Bundle of HR practices or policies oriented towards some overarching goal" is the definition of the HRM system.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Nyathi et al [40] Divide the HRM system into three categories: philosophy, practices, and policy. "Bundle of HR practices or policies oriented towards some overarching goal" is the definition of the HRM system.…”
Section: Studymentioning
confidence: 99%
“…Parry & Tyson [39]underscore the anticipated enhancements arising from e-HRM implementation, ranging from improved service delivery to heightened strategic focus and overall efficiency. Nyathi et al [40] contribute by categorizing the HRM system into three distinct levels-philosophy, practices, and policies-offering a nuanced perspective on the components integral to effective HRM. Ruël et al [5] align with the concept of e-HRM, emphasizing compliance with the hierarchical structure of HRM system components, encompassing practices, policies, and philosophy.…”
Section: Ruël Et Al [5]mentioning
confidence: 99%
“…Bondarouk et al (2017) found this to be the most important context for influencing e-HRM adoption and its consequences. Moreover, Nyathi and Kekwaletswe (2023) found that employee performance mediates the relationship between e-HRM use and organisational performance, thus emphasising the benefits of informating in terms of improved information flows, involvement of employees in decision making and giving them new development opportunities. However, this rests on employees' perception of e-HRM as useful and easy to use in achieving their goals (Zhou et al, 2022;Nyathi & Kekwaletswe, 2023).…”
Section: People Contextmentioning
confidence: 99%
“…Ultimately, this can reduce the performance and effectiveness of the organisation (Panos & Bellou, 2016). Users' resistance to e-HRM may be related to inadequate change management (Reddick, 2009), ineffective e-HRM implementation processes (Reddington & Hyde, 2008), security/privacy fears (Reddick, 2009;Lau & Hooper, 2009), users' e-HRM knowledge (Zhou et al, 2022) poor training in using e-HRM (Parry & Tyson, 2011;Nyathi & Kekwaletswe, 2023) and perception that they are 'doing HR's job', with a consequence of actual or perceived work overload (Martin & Reddington, 2010). Gardner et al (2003) found that the adoption of e-HRM simply replaces administrative duties with technological support for employees.…”
Section: Australasian Journal Of Information Systemsmentioning
confidence: 99%
“…Consistent research results explain that the indirect impact of the use of e-hrm on organizational performance is positive and statistically significant. (Nyathi & Kekwaletswe, 2023).Employe performance berpengaruh signifikan terhadap employee productivity dengan koefisien regresi sebesar 0.947, dengan nilai probabilitasnya < 0,05 (0.000) dan nilai CR sebesar 10.333.…”
Section: H3: Employee Performance Memiliki Pengaruh Terhadap Employee...mentioning
confidence: 99%